Perceptions and Attitudes of Men towards their Wives’ Menopausal Transition Period (Medico Legal Update, 2021)
Background: Menopause is a natural process that occurs in women’s life as a part of normal aging.Recognition of women’s needs during menopause is considered important and required to maintain goodquality of life.Objective: This study aims at exploring the perceptions and attitudes of men towards their wives duringmenopause in Jordan.Method: This study used the descriptive approach. 104 men were randomly chosen, for data collection, theAttitude towards Menopause was adopted in this study.Results: Study results concluded that the men’s perceptions and attitudes toward their wives experiencingmenopause in Jordan, ranged from (1.83– 1.30), where the whole dimension scored a total mean of (1.55),which is of a medium level. The study also concluded that there is no relationship at level of (0.05) betweenmen’s perceptions and attitudes toward their wives experiencing menopause in Jordan and age, nationality,educational level and marry year. And the results showed that there are no statistically significant differencesin the men’s perceptions and attitudes according to the age, and nationality in Jordan. While, there arestatistically significant differences in theirperceptions and attitudes with the Marry year in favor of 1-10-yearcategory.Conclusion: Advising men to engage in various activities with his wife during menopause can positivelyaffect their attitudes, improve their body image.